A Long-Term Survey on the Shoreline Changes of Gulf of Oman Coasts (Makran) - Ghaderi, Danial; Rahbani, Maryam (Ocean science journal, 2025)
The shoreline constitutes a highly dynamic segment within the nearshore zone, subject to continuous erosion and accretion influenced by hydrodynamic or morphological factors. Given its interaction with human activities, the type and intensity of shoreline changes can have implications for both the environment and human activities. With this respect, this study is conducted to explore the long-term shoreline changes along the western Makran coast. The study period spans from 1986 to 2020, utilizing Landsat Satellite 5, 7, and 8 images. The indexes of shoreline change envelope (SCE), net shoreline movement (NSM), end point rate (EPR), and linear regression rate (LRR) have been employed to investigate the changes and rate of changes in shoreline during these 34 years. The results reveal that over 81km and 54.4 km of the shoreline exhibit accretion rates exceeding 2.0 m/year and erosion rates exceeding 2 m/year, respectively. Approximately 184.4 km of the shoreline experiences low change rates (− 0.5 to 0.5 m/year). Although the shore of Makran is located in the open sea, is relatively faced with low level of shoreline changes which is more or less comparable with the shorelines inside the semi-enclosed body of water of the Persian Gulf. We also criticized the trustworthiness of the Kalman Filter for predicting shoreline change in conditions where the shore was faced with nonlinear changes. Although the Kalman Filter method demonstrated acceptable accuracy in 55.3% of the shoreline, overall, it exhibits limitations, emphasizing the necessity to consider coastal type and elevation in shoreline predictions.